A calculation model of TC4 shot peening residual stress based on elastic-plastic theory. (May 2023) - Wang, Yanzhong; Zhang, Wei; Yu, Bo; Li, Zhenpeng; Liu, Yang
Shot peening is widely used in automobile, aviation, and other industries because it can change the fatigue strength of metal structures by introducing residual compressive stress field on the surface and significantly improve the fatigue life of mechanical structures. In order to improve the surface properties of parts after shot peening, an analysis method for rapidly predicting residual stress of parts surface during shot peening is proposed. During the analysis, an elastoplastic impact model of shot was established, and stress–strain laws in three processes of elastic loading, plastic deformation and stress release were studied. The residual stress under different shot peening parameters was predicted by considering the plastic strengthening effect of TC4 (Ti-6Al-4V). A TC4 shot peening test was performed and residual stress was measured, and the results are consistent with the model predictions, which verified correctness of the model.